Automated Light Controller Using Fuzzy Logic - Saleh, Morad Ali Ambarem. (2008)
This study describes the implementation of fuzzy logic in designing fuzzy automated light controller. The fuzzy controller controls the number of lamps lighted up based on the number of people inside the room. Its main objective is to demonstrate how fuzzy logic can minimize the number of lamps used and therefore reduce the electricity consumption. In this study, fuzzy logic controller has been implemented and tested to predict the behaviour of the controller under different light conditions by monitoring the membership function parameters. In a conventional light controller, the lamps change according to user’s specification. The light will remain on if the user forgets to switch off the light. Even if an automated light controller exist, at most the system can only be controlled as on and off without being able to adapt with dynamic inputs. Fuzzy logic offers a better method than conventional control methods, especially in the case of counting the number of people and how much the light intensity is needed. In this study, fuzzy logic has the ability to make decision as to how much the light intensity is needed by controlling the number of lamps in the room according to the number of people who have entered or left the room. On the other hand, the conventional light controller does not have the ability to solve this kind of issues. It would be more practical to let more lamps "on" if the light intensity needed is very bright. A conventional method controller for this decision is difficult to find while fuzzy logic controller simplifies the task. This study has achieved its objective, which is to design a fuzzy logic system integrated with hardware circuit of automated light controller using fuzzy logic to control light intensity in a room. In this study, tests cases have illustrated that fuzzy logic control method could be a suitable alternative method to conventional control methods that could save electricity consumption and offers ease of use to human being.